Susceptibility of Egg Stadia of Walang Sangit (Leptocorisa acuta thunb.) To Entomopathogenic Fungi Beauveria Bassiana (bals.) Vuill. and Metarhizium spp. From various rhizosphere - Effi Yudiawati (Baselang, 2023)
This study aims to determine the pathogenicity of the entomopathogenic fungi Beauveria bassiana (Bals.) Vuill and Metarhizium spp. isolated from various locations. against Walang Sangit (Leptocorisa acuta Thunb.) eggs. In this experiment, the egg group of Leptocorisa acuta and 5 isolates of entomopathogenic fungi were used, namely Bb5a, Bb4b, Bb1e, Met3b, and Met1a. Application of entomopathogenic fungi was carried out by spraying entomopathogenic fungi according to the treatment using hand sprayer in each treatment as much as 2 ml. Conidial concentration of each isolate used for testing was 108 conidia/ml. The variables observed were L. acuta egg mortality, 1st instar L. acuta nymph mortality, and length of 1st instar L. acuta nymph death. Observational data were analyzed statistically by Analysis of Variance (Anova), if it had a significant effect then it was continued with the DNMRT test at 5% level. The results showed that isolates of entomopathogenic fungi Bb4b and Met3b had a significant effect on L. acuta egg mortality, 1 L instar nymph mortality .acuta, and time of death of 1st instar nymph L.acuta.